Health body priming and food choice: An eye tracking study. (March 2019) - Manippa, Valerio; van der Laan, Laura N.; Brancucci, Alfredo; Smeets, Paul A.M.
Highlights: Chosen foods are gazed more than non-chosen foods. High-calorie products are gazed more than low-calorie products. Overweight and underweight body primes may activate specific health worries. Gaze bias theory is only partially applicable to food choice. Abstract: The "gaze bias theory" suggests that people tend to look longer at items that are eventually chosen. This was not entirely confirmed for food choice, a complex phenomenon influenced by many factors. Although it has been shown that health-related primes affect both consumer attention and choice, the effect of unhealthy body shape primes on these outcomes is largely unknown. Therefore, we here investigated how body primes, namely normal weight (NW), severely overweight (OW) and severely underweight (UW) body shapes, influenced attention and choice for low-calorie food (LcFd) and high-calorie food (HcFd). We hypothesized that OW and UW primes would activate opposing health goals (weight-loss vs. weight-gain respectively). Fifty normal weight sated females completed a primed food choice task in which choices between a LcFd and HcFd, matched for subjective liking, were presented after control or human body shapes (NW, UW or OW). In each trial participants had to identify the shape (i.e., non-human, human male or human female) and then choose the food they wanted to eat at that moment. Gaze was recorded by an eye tracker. Results showed that, although primes did not influence the choice, the total dwell time on chosen HcFd was higher when preceded by an OW prime compared with chosen LcFd and chosen HcFd preceded by an UW prime. Also, both total dwell time and the number of fixations were higher for chosen food compared with non-chosen food as well as for HcFd compared with LcFd without a corresponding higher proportion of HcFd choice. Overall, these data shed light on the interactions between attention, health body priming and food choice.